Japanese Polytechnic Diplomacy in Indonesia: Establishing Electrical Engineering Polytechnic Institute of Surabaya (EEPIS) as Japan's Higher Vocational Ambassador to Developing Countries through Triangular Development Cooperation - Susanto, Siti Rokhmawati (Jurnal Hubungan Internasional, 2021)
This paper aims to examine implications of Japan's ‘polytechnic diplomacy' approach as its international development strategy towards Indonesia. Utilizing concepts and framework related to international development assistance, triangular development cooperation (TDC), and public diplomacy, this paper argues that development fund disbursement affects interactions among actors, not only in bilateral context but also multilaterally. Mainly, on how this activity transform an aid recipient into a potential partner for the donor's future international development programs. It is occurred due to the facilitation of donor's triangular development cooperation (TDC). The aid recipient's success story thus prompted the donor to perceive them as its development ambassador. the pattern continues as the donor attempts to disseminate the formula to other developing countries. The Electrical Engineering Polytechnic of Surabaya (EEPIS) exemplifies the case on how a specific foreign aid approach raises global multiplier effects to both aid provider and recipient.